ARCHETYPAL EFL READERS: PRELIMINARY EMPIRICAL EVIDENCE SUBSTANTIATED FROM SELECTED DISCRIMINATING VARIABLES - Gunadi H. Abd. Sulistyo; Suharmanto Suharmanto (TEFLIN, 2007)
The study is an attempt to empirically examine factors that differentiate EFL readers with different EFL reading proficiency levels. Four selected factors believed to play a role in reading comprehension are considered, namely: linguistic knowledge, reading strategies, text structure knowledge, content and world background knowledge. Discriminant analysis was employed to scrutinize the data collected on these variables. The analysis wraps up, revealing that advanced EFL readers, while they are sufficiently equipped with formal schemata that necessarily embrace both linguistic knowledge and text structure knowledge, can be speculated to consist of three groups: those who fail to activate their relevant schemata, those who fail to use their reading strategies, and those who can function both content and world background knowledge and their reading strategies with ease.